Template-free synthesis of one-dimensional hierarchical NiO nanotubes self-assembled by nanosheets for high-performance supercapacitors. Issue 9 (July 2016) - Liu, Aifeng; Che, Hongwei; Mao, Yuanxin; Wang, Yuqiao; Mu, Jingbo; Wu, Chunxia; Bai, Yongmei; Zhang, Xiaoliang; Wang, Guangshuo
Abstract: In this work, one-dimensional hierarchical NiO nanotubes from the self-assembly of nanosheets have been successfully prepared via a facile template-free solvothermal method followed by an annealing process. The as-synthesized NiO nanotubes have an internal tubular diameter of 350 nm and lengths of 2.0–4.0 μm. And a possible formation mechanism for hierarchical NiO nanotubes is also investigated. When used as electrode materials for supercapacitors, these NiO nanotubes exhibit a high specific capacitance of 919 F g −1 at 1.0 A g −1 and a specific capacitance retention of 94.7% after 2000 continuous charge–discharge cycles at 2.0 A g −1 . This superior electrochemical performance of NiO nanotubes electrode can be ascribed to the synergetic effect of its open tubular architectures and the short diffusion lengths in the nanosheets-based building blocks, allowing them to be a promising electrode material for supercapacitor applications.